ANALISA PENYEBAB KEMACETAN DI JALAN SLAMET RIYADI (PASAR KUTO) MENUJU ARAH JEMBATAN MUSI 4 - Setiawati, Mira; Royan, Noto; Wijaya, a Pasha (Universitas Muhammadiyah Palembang, 2020)
The traffic jam that occurred on the Slamet Riyadi road towards the Palembang Musi 4 Bridge was due to the large volume of vehicles passing through the road due to the diversion of road users who chose to cross the musi 4 bridge so that the volume of vehicles passing on the road grew day by day, causing even the density level higher and cause congestion during rush hours, namely between 07.00-09.00 WIB, between 12.00-14.00 WIB and between o'clock. 4:00 PM to 6:00 PM WIB.By conducting research and calculations, it is found that the capacity of Slamet Riyadi Street is 2291 SMP / Hour, the worst service level, is F for the morning, occurs on Wednesday and Friday. The worst service level in the afternoon is E. The worst service level in the afternoon is F which occurs on Monday, Tuesday and Thursday, while the capacity of the Major Memet Sastra Wirya Road section is 2291 SMP / Hour and also the worst service level is F for the morning occurs on Friday. The worst service level, D for daytime, occurs on Thursday and Friday. The worst service level for the afternoon is F occurs on Friday.The cause of the congestion that occurs is caused by some roads littered with garbage from landfills, public transports that carry passengers, some roads are used as pedicab bases, many vehicles violate traffic regulations, and others.